Membangun Karakter Islami Melalui Pembelajaran Inovatif Pai: Implementasi Kontekstual, Research Based Learning, Problem Based Learning, Dan Quantum Theaching - Lestari, Septia Sri; Ismail, Fajri; Astuti, Mardiah (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
From an Islamic perspective, theoretical character education has actually existed since Islam was revealed in the world along with the sending of the Prophet Muhammad SAW. to improve or perfect human morals (character). The research method used in this article is a library research approach or qualitative literature study. This method is carried out by analyzing or searching for objects such as books, articles, scientific journals, documents and other relevant literature to be used as references. The concept of learning is essentially an educator's activity in teaching students. Contextual teaching and learning is a learning concept that helps teachers link the material they teach so as to encourage students to make connections between the knowledge they have and its application in their daily lives. The Research Based Learning (RBL) model applies research activities or simple experiments carried out by students. The problem-based learning model is a teaching and learning process that presents contextual problems so that students are stimulated to learn. The quantum teaching method can help create an effective learning environment through the utilization of elements in students. Islamic Religious Education is a deliberate and planned action to prepare students so that they can recognize, understand, absorb, and believe in the teachings of Islam.